Mapping peat thickness and carbon stocks of the central Congo Basin using field data - Crezee , Bart; Dargie, Greta C.; Ewango, Corneille E. N.; Mitchard , Edward T. A.; Emba B, Ovide; Kanyama T, Joseph; Bola, Pierre; Ndjango, Jean-Bosco N.; Girkin, Nicholas T.; Bocko, Yannick E.; Ifo, Suspense A.; Hubau , Wannes; et al. (Springer, 2022)
The world’s largest tropical peatland complex is found in the central Congo Basin. However, there is a lack of in situ measurements to understand the peatland’s distribution and the amount of carbon stored in it. So far, peat in this region has been sampled only in largely rain-fed interfluvial basins in the north of the Republic of the Congo. Here we present the first extensive field surveys of peat in the Democratic Republic of the Congo, which covers two-thirds of the estimated peatland area, including from previously undocumented river-influenced settings. We use field data from both countries to compute the first spatial models of peat thickness (mean 1.7 ± 0.9 m; maximum 5.6 m) and peat carbon density (mean 1,712 ± 634 MgC ha−1; maximum 3,970 MgC ha−1) for the central Congo Basin. We show that the peatland complex covers 167,600 km2, 36% of the world’s tropical peatland area, and that 29.0 PgC is stored below ground in peat across the region (95% confidence interval, 26.3–32.2 PgC). Our measurement-based constraints give high confidence of globally significant peat carbon stocks in the central Congo Basin, totalling approximately 28% of the world’s tropical peat carbon. Only 8% of this peat carbon lies within nationally protected areas, suggesting its vulnerability to future land-use change.
Keywords: Carbon cycle; Freshwater ecology; Hydrology; Tropical ecology